The Trend and Seasonal Change of Sediment in the East China Sea Detected by GRACE - Le Chang; He Tang; Shuang Yi; Wenke Sun (Geophysical Research Letters)
Abstract The deposition of land sediments onto the broad continental shelf of the East China Sea (ECS) is controlled by complex, dynamic hydrological mechanisms. In this study, we apply the data from Gravity Recovery and Climate Experiment (GRACE) satellite to detect the gravity signal caused by changes in sedimentation. The GRACE‐observed gravity signal is separated into the individual contributions using multisource data. After correction of each known individual signal, the sediment‐caused gravity change signal is used to invert for the sediment mass change in the ECS using a space domain inverse method. The results indicate that the total GRACE‐inverted sediment deposition rate was 0.82 ± 0.3 Gt/year from 2005 to 2015, which is in agreement with in situ sediment observations. The seasonal sediment change is also calculated and discussed. It is caused by sediment transport between the ECS and the Yellow Sea.